Investigation of Heat Transfer Characteristics and Electrical Conductivities in NaCl, KCl, and NaNO3 Solutions - Nigar Kantarci-Carsibasi; Jana Masalmah; Ozlem Simsek (Advances in Technology Innovation, 2025)
This study aims to optimize heat exchanger systems by investigating the effects of water-soluble salts (NaCl, KCl, and NaNO3) on heat transfer rates and electrical conductivity. Experiments are conducted using plate-type (PHE) and double-pipe (DPHE) heat exchangers. The heat transfer coefficient ranged from 1.5–6.5 kW/m²K in PHE and 3.5–20 kW/m²K in DPHE. NaCl achieves the highest heat transfer rates, followed by KCl and NaNO3, all outperforming pure water. Electrical conductivity peaks at 1 MHz, decreasing afterward, with NaCl and KCl showing higher conductivity than NaNO3. Conductivity increases with temperature, peaking at 70°C, and is more sensitive to temperature for KCl and NaCl. This dual-focus study correlates thermal and electrical properties, illustrating how variations in salt type, concentration, and temperature influence ion behavior, which plays a critical role in optimizing industrial heat transfer and electrical conductivity processes.